Nigeria and the African Continental Free Trade Agreement: The Two-Level Game Analysis - Adebimpe, Teslim Ademola; Badru, Ronald Olufemi (Kashere Journal of Politics and International Relations, 2025)
The Nigeria’s engagement with the African Continental Free Trade Agreement (AfCFTA) highlights the complexities of balancing domestic concerns with international commitments. Without doubt, the foreign policy environments comprising the domestic and international levels play key roles in determining the outcomes of foreign policy engagements of a nation. However, what is more important and requires understanding is the linkage between the two levels and the effect of this on the conduct of foreign policy. This is the focus of this paper as it undertook an analysis of the ratification of the African Continental Free Trade Agreement (AfCFTA) by Nigeria using the two-level game theoretical framework in order to demonstrate the linkage and influence of the actors at the domestic and international levels on the conduct of Nigeria’s foreign policy. The paper adopted content analysis method using secondary sources. From the analysis, it was established that the delay and eventual ratification of the AfCFTA by Nigeria was premised on the need to balance between the concerns and interests of the domestic pressure groups and the international standing of the country as well as the expected benefits that may accrue to the country from the AfCFTA. It was therefore recommended that for Nigeria’s future foreign policy engagements, all the concerned actors and interest groups that may be impacted by the foreign policy outcomes should be involved in the formulation and implementation of the policy.